Treatment of COVID-19: Antivirals, Antibody Products, Immunomodulators, Antithrombotic Therapy, and Supplements - Asuman İnan; Sibel Bolukçu (Cam & Sakura Medical Journal, 2023)
With the advent of the pandemic, the landscape of treatment options has undergone rapid transformations in response to evolving viral variants. Current guidelines advocate tailoring treatments based on disease severity and the distinction between outpatient and inpatient settings. Remdesivir is endorsed for hospitalized cases, whereas molnupiravir is recommended for managing mild to moderate coronavirus disease-2019 (COVID-19) in individuals at high risk of progressing to severe disease. Baricitinib holds Food and Drug Administration (FDA) approval in the United States for use in hospitalized adults requiring supplemental oxygen, non-invasive or invasive mechanical ventilation, or extracorporeal membrane oxygenation. Furthermore, dexamethasone is indicated for severely ill COVID-19 patients who require supplemental oxygen or ventilator support. Notably, tocilizumab has demonstrated limited efficacy in reducing the risk of disease progression. The FDA has granted Emergency Use Authorization for bebtelovimab, specifically for the treatment of mild to moderate COVID-19. Tixagevimab and cilgavimab have received FDA authorization for emergency use as pre-exposure prophylaxis against COVID-19. Although there is a recommendation against the use of an intermediate dose of low-molecular-weight heparin in critically ill COVID-19 patients, supported by moderate-level evidence, this recommendation does not extend to outpatient settings. However, there is insufficient evidence to endorse or discourage the use of supplements for treating COVID-19, both in non-hospitalized and hospitalized patients.